A feasibility study on methods of construction over peat soils - Keli, H. (Universiti Malaysia Sarawak, UNIMAS, 2006)
The purpose of this study is to discuss the various methodology of construction used over peat soil. The methods highlight here includes fill and excavation methods, methods for accelerating consolidation, ground improvement techniques for reducing deformation, grouting techniques, application of geosynthetics techniques and soil stabilization.